2017
DOI: 10.1007/s13258-017-0624-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive miRNA-135a inhibits breast cancer cell proliferation by targeting ELK1 and ELK3 oncogenes

Abstract: Breast cancer is the most common malignant disease amongst women. miRNAs are small, non-coding RNAs that regulate gene expression, thus have the potential to play an important role during cancer development. Emerging evidence shows that miR-135a is down-regulated in breast cancer cells, but the functional roles of miR-135a in breast cancer cells remains unexplored. For this purpose, we investigated the expression of miR-135a in breast cancer cells and explored its functional role during breast cancer progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Other ndings of the present study indicated that has-miR-135 was downregulated only in the patients with a good response to the treatment. Some studies have shown that the induction of miR-135a expression in different types of cancers could suppress cell proliferation through target genes (c-MYC, STAT6, SMAD5, and BMPR2), and miR-135a has also been introduced as a potential predictor of treatment outcome in some cancers [44]. This study con rmed that these target genes are signi cant targets of has-miR-135 in achalasia (Table 4).…”
Section: Discussionsupporting
confidence: 61%
“…Other ndings of the present study indicated that has-miR-135 was downregulated only in the patients with a good response to the treatment. Some studies have shown that the induction of miR-135a expression in different types of cancers could suppress cell proliferation through target genes (c-MYC, STAT6, SMAD5, and BMPR2), and miR-135a has also been introduced as a potential predictor of treatment outcome in some cancers [44]. This study con rmed that these target genes are signi cant targets of has-miR-135 in achalasia (Table 4).…”
Section: Discussionsupporting
confidence: 61%
“…Our results suggest that has-miR-135 is down-regulated only in good treatment response achalasia patients. Some studies showed that the induction of miR-135a expression in different types of cancers could suppress cell proliferation through target genes (c-MYC, STAT6, SMAD5, and BMPR2) and also miR-135a has been introduced as a potential predictor of treatment in some cancers [44]. We could show that these target genes are significant targets of has-miR-135 in achalasia.…”
Section: Deregulation Of Certain Individual Mirnas Compromises Immunementioning
confidence: 72%
“…On the other hand, miRNA-135a showed a inhibitive role during the migration and invasion of lung cancer cells, due to targeting a transcription factor [19] . However, the functions and mechanisms of miRNA-135a during tumors are largely unknown [20][21][22][23] . Recent studies have demonstrated that miRNA-135a is up-regulated in CC cell lines SW480 and SW620, while in our study, the expression levels of miRNA-135a were significantly increased in CC tissues, which was in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 99%